2011
DOI: 10.1007/s12600-011-0198-9
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of cocooned pupae and adults of the parasitoid Microplitis mediator to selected insecticides

Abstract: The braconid parasitoid Microplitis mediator (Haliday) is a key natural enemy of the cabbage moth, Mamestra brassicae (L.), in Europe. In the context of an Integrated Pest Management approach, the use of selective insecticides is essential for the conservation of naturally occurring beneficial arthropods. The present laboratory study investigated the side effects of six insecticides applied at recommended field rates on adults and cocooned pupae of M. mediator. Male and female parasitoids were paired in drum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Although there is little information about the side effects of spirotetramat on other natural enemies, the available studies have similarly categorized this lipid biosynthesis inhibitor as harmless to other natural enemies, such as the predators Episyrphus balteatus (Degeer) (Diptera: Syrphidae) and Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) (Schnorbach et al 2008;Moens et al 2011) and the parasitoids Microplitis mediator (Haliday) (Hymenoptera: Braconidae), Coccidoxenoides perminutus Girault (Hymenoptera: Encyrtidae) and Anagyrus sp. near pseudococci (Hymenoptera: Encyrtidae) (Mansour et al 2011;Moens et al 2012). Therefore, based on these results, and on the side effects observed in our study, spirotetramat could be included in IPM programs where C. montrouzieri is a key natural enemy.…”
Section: Discussionmentioning
confidence: 63%
“…Although there is little information about the side effects of spirotetramat on other natural enemies, the available studies have similarly categorized this lipid biosynthesis inhibitor as harmless to other natural enemies, such as the predators Episyrphus balteatus (Degeer) (Diptera: Syrphidae) and Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) (Schnorbach et al 2008;Moens et al 2011) and the parasitoids Microplitis mediator (Haliday) (Hymenoptera: Braconidae), Coccidoxenoides perminutus Girault (Hymenoptera: Encyrtidae) and Anagyrus sp. near pseudococci (Hymenoptera: Encyrtidae) (Mansour et al 2011;Moens et al 2012). Therefore, based on these results, and on the side effects observed in our study, spirotetramat could be included in IPM programs where C. montrouzieri is a key natural enemy.…”
Section: Discussionmentioning
confidence: 63%
“…Merthiocarb and methomyl also increased female infertility rate. Different studies have reported that pirimicarb did not affect the biological parameters of T. pretiosum (Carvalho et al 2001), however, other authors found that this product caused high mortality when adults of other parasitoids were exposed to dry residues or the direct spray method (Desneux et al 2004, Moens et al 2012. Bueno et al (2008) demonstrated that methomyl significantly reduced parasitism viability when applied in the T. pretiosum immature stages.…”
Section: Discussionmentioning
confidence: 92%
“…For example, no or negligible reduction in survival was observed in the ground beetle Bembidion lampros, 12 the coleopteran predator Cryptolaemus montrouzieri, 13 the rove beetle Atheta coriaria 14 or the parasitoid Microplitis mediator. 15 Also, the parasitoid Leptomastix dactylopii 13 and the hoverfly Episyrphus balteatus 12,16 suffered neither mortality nor sublethal effects due to flonicamid. However, several authors have reported lethal and sublethal effects on non-target organisms from a range of taxa.…”
Section: Introductionmentioning
confidence: 98%